Stimulating Development Method to Promote Health in Children with Intellectual Disabilities During the COVID-19 Pandemic Crisis: A Systematic Literature Review - Benjayamas Pilayon; Pairin Yodsuban; Niruwan Turnbull; Chanicha Chaitonthueng; Juthaluck Saentho; Muhamad Zulfatul A'la; Rondhianto Rondhianto (Universitas Jember, 2024)
During the COVID-19 pandemic, caregivers and parents play a crucial role in supporting individuals with intellectual disabilities, necessitating adjustments in self-care and the acquisition of essential caregiving skills. Research efforts are focused on developing effective health promotion programs and understanding the pandemic's impacts on individuals with intellectual disabilities, highlighting the importance of systematic literature reviews in synthesizing knowledge for effective caregiving during this crisis. This research aimed to systematically review literature related to stimulating development for health promotion in children with intellectual disabilities during the COVID-19 pandemic crisis. A systematic literature review searched keywords related to variables and sample groups. Data sources were electronic databases, including Scopus, ScienceDirect, Web of Science, and PubMed. The research included studies on the care and health support of individuals with intellectual disabilities over the past 10 years, from September 1, 2021, to January 1, 2022. Among these studies, 8 were selected, focusing on stimulating development and health support for children with intellectual disabilities. The systematic review yielded four programs: 1) Health education in classrooms to promote the health of individuals with intellectual disabilities, 2) Health record registration and health check-ups to promote health, 3) Training with equipment, and 4) Weight reduction and body mass index improvement programs to promote health among individuals with intellectual disabilities. The literature review revealed an increase in knowledge about programs for stimulating development and promoting health in children with intellectual disabilities during the COVID-19 pandemic crisis.